Efficient illumination design and energy saving through occupancy control for building - Lakshmanan R.; Ramasamy A.K.; Ahmed S.K.; Sinnadurai R. (IEEE Computer Society, 2023)
In any nation, energy is the fuel for its economic development. Realizing the utmost importance of energy, enormous efforts have to be taken in order to secure the energy availability of a nation. Therefore, it is necessary to increase the efficiency of electric energy usage and make use of the renewable energy sources in order to extend the availability of these fuel resources. This paper focuses on the efficient illumination design and occupancy of the main building of Asia Pacific University of Technology & Innovation (APUTI). A detailed load and energy audit was done for APUTI main building. For efficient illumination design the existing lighting design was reviewed and the potential energy saving by delamping the lights were determined and validated with actual photometric measurements. The energy saving through occupancy control was also determined. 2013 IEEE.